Optical Fiber Communication Conference/National Fiber Optic Engineers Conference 2013 2013
DOI: 10.1364/ofc.2013.ow1d.4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Optical Modulators in LTE RoF System with Nonlinear Compensator for Enhanced Power Budget

Abstract: Nonlinear propagation compensation for LTE-RoF system is experimentally demonstrated with proposed DMFD and EMFD methods. We discovered that the RoF dithering frequency requirement have to be much smaller with an average improvement of ~5.35 dB.OCIS codes: (060.0060) Fiber Optics and Optical Communications; General; (060.5625) Radio Frequency Photonics Introduction and the Proposed SystemThe 3 rd generation partnership program (3GPP) long term evolution (LTE) technology experiences limited cell radius of 1 km … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…The transmission characteristics of multi-IF carriers with an LTE baseband signal were also mathematically investigated in [11]. Most of the previous investigations were mainly focused solely on the performance of the optical transmission [15]- [18].…”
Section: Demonstration Of Mobile Fronthaul Test Bedmentioning
confidence: 99%
“…The transmission characteristics of multi-IF carriers with an LTE baseband signal were also mathematically investigated in [11]. Most of the previous investigations were mainly focused solely on the performance of the optical transmission [15]- [18].…”
Section: Demonstration Of Mobile Fronthaul Test Bedmentioning
confidence: 99%
“…Recently, a novel scheme based on MZM dual drive to combine hybrid coupler and double parallel MZM an optical single side band that has been conducted [1,2]. Investigated Direct Modulation (DM) and External Modulation (EM), and direct modulator on QAM (Quadrature Amplitude Modulation) has exhibits to mitigate SBS (stimulated Brillouin scattering) and optimization nonlinear compensated for LTE (Long Term Evolution)-RoF with varied launch power for enhanced power budget [3]. Another line of research is aimed to demonstrate of the nonlinear compensation LTE-RoF based on DMFD (Direct Modulation Frequency Dithering) and EMFD (External Modulation Frequency Dithering) also to mitigate SBS including analysis of QPSK (Quadrature Phase Sift Keying), 16 QAM, and 64 QAM scheme [4].…”
Section: Introductionmentioning
confidence: 99%
“…The principle of operation is based on simple amplifying and forwarding RNs with RoF acting as the interface between the eNB and RN [4][5][6][7][8]. In other words, instead of eNB, the RN delivers the LTE signal to the UE at the cell edge.…”
mentioning
confidence: 99%
“…As a solution, we recently proposed a direct modulation based frequency dithering (DMFD) method for nonlinear compensation specifically designed for the LTE RoF system [5], which enabled the use of higher optical launch powers. Further optimizations of this method were carried out in the perspective of optical modulators [6] and dithering frequency f d with higher order modulations [7]. In [6], it is shown that DMFD method introduces an additional ~3 dB optical power penalty in comparison to external modulation while imposing a lower cost.…”
mentioning
confidence: 99%
See 1 more Smart Citation